Generation of Otic Sensory Neurons from Mouse Embryonic Stem Cells in 3D Culture - Perny, Michael; Ting, Ching-Chia; Kleinlogel, Sonja; Senn, Pascal; Roccio, Marta (Frontiers in Cellular Neuroscience, 2017)
The peripheral hearing process taking place in the cochlea mainly depends on two distinct sensory cell types: the mechanosensitive hair cells and the spiral ganglion neurons. The first respond to the mechanical stimulation exerted by sound pressure waves on their hair bundles by releasing neurotransmitters and thereby activating the latter. Loss of these sensorineural cells is associated with permanent hearing loss. Stem cell-based approaches aiming at cell replacement or in vitro drug testing to identify potential ototoxic, otoprotective or regenerative compounds have lately gained attention as putative therapeutic strategies for hearing loss. Nevertheless, they rely on efficient and reliable protocols for the in vitro generation of cochlear sensory cells for their implementation. To this end, we have developed a differentiation protocol based on organoid culture systems, which mimics the most important steps of in vivo otic development, robustly guiding mouse embryonic stem cells (mESCs) towards otic sensory neurons. The stepwise differentiation of mESCs towards ectoderm was initiated using a quick aggregation method in presence of Matrigel in serum-free conditions. Non-neural ectoderm was induced via activation of Bone Morphogenetic Protein (BMP) signaling and concomitant inhibition of Transforming Growth Factor beta (TGF-β) signaling to prevent mesendoderm induction. Preplacodal and otic placode ectoderm was further induced by inhibition of BMP signaling and addition of Fibroblast Growth Factor 2 (FGF-2). Delamination and differentiation of SGNs was initiated by plating of the organoids on a 2-dimensional Matrigel-coated substrate. Supplementation with brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3) was used for further maturation until 15 days of in vitro differentiation. A large population of neurons with a clear bipolar morphology and functional excitability was derived from these cultures. Immunostaining and gene expression analysis performed at different time points confirmed the transition trough the otic lineage and final expression of the key otic sensory neuron markers. Moreover, the stem cell-derived otic sensory neurons exhibited functional electrophysiological properties of native SGNs. Our established in vitro model of otic sensory neurons development can be used for basic developmental studies, for drug screening or for the exploration of their regenerative potential.